2002
DOI: 10.1017/s0068246200002105
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research on the City and Territory of Nepi (VT)

Abstract: NUOVE RICERCHE SULLA CITTÀ E IL TERRITORIO DI NEPI (VT)In questo articolo si rendono noti i risultati dei lavori nella città e nel territorio di Nepi (VT). Vengono dati un resoconto ccmpleto dei reperti di superficie rinvenuti da Torre Stoppa e da Il Pizzo, datati all'età del bronzo, e la relazione finale del piccolo scavo vicino San Tolomeo, dentro la stessa città, che ha riportaio alia luce un mosaico di prima eta imperiale. Vengono inoltre presentate altre due relazioni in forma preliminare. La prima fornis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…I created a series of least-cost paths between the main centres in the region around Nepi (Rajala 2002). These paths suggested that the Treia valley could have been an important route of communication in the past.…”
Section: The Meaning Of Fluvial Landscapes In the Nepi Areamentioning
confidence: 99%
See 3 more Smart Citations
“…I created a series of least-cost paths between the main centres in the region around Nepi (Rajala 2002). These paths suggested that the Treia valley could have been an important route of communication in the past.…”
Section: The Meaning Of Fluvial Landscapes In the Nepi Areamentioning
confidence: 99%
“…This paper compares two geographically contrasting areas in central Italy with similarities in fluvial hydrology. It is based on my PhD thesis (Rajala 2002) that showed certain correlations between fluvial characteristics and human settlement in my two case study areas ( Fig. 1) on the two sides of the Tiber in central Italy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nepi Survey Project (di Gennaro et al 2002;Rajala 2006;di Gennaro et al 2008) that carried out a surface collection in the territory of Nepi (ancient Nepet), north-west of Rome in 1999 and 2000 under the umbrella of the Tiber valley project (Patterson and Millett 1998;Patterson et al 2000;Coarelli and Patterson 2008), provides such evidence. The 'Romanisation of a Faliscan town' project, funded by the British Academy, analysed the Roman pottery and ceramic building material (CBM) from this survey in order to study the character and continuity of Roman rural and suburban settlement around this minor Roman town.…”
Section: Introductionmentioning
confidence: 99%